PENERAPAN HUKUMAN AKIBAT KELALAIAN MENGEMUDIKAN KENDERAAN BERMOTOR MENGAKIBATKAN ORANG MENINGGAL DUNIA (STUDI KASUS DI PENGADILAN NEGERI PADANGSIDIMPUAN) - Muhammad Fasial (JUSTITIA : Jurnal Ilmu Hukum dan Humaniora, 2020)
Research on the application of the punishment for the perpetrator by lifting a formula of misdemeanment raised as follows, how does the application of punishment to the perpetrator of a crime resulting from negligence driving a motor vehicle cause others to die and what are the contributing factors to the criminal offence of negligence driving a motor vehicle causing another person to die?.  The research methods that the authors used in the writing of this study are normative research that uses skunder data sources and in the form of legislation, as well as the Padangsidimpuan District Court Decision which has to do with this research is the research conducted with the results of the author's interview with the respondent and also conducts research on the data and files related to this research by conducting Field Research (Library Research) and Field Research (Field Research). The application of punishment against the perpetrators of crimes resulting from negligence driving a motor vehicle causes others to die in the Jurisdiction of padangsidimpuan District Court based on legal facts both through witness statements, statements of the defendant, and evidence tools, in addition, also based on juridical considerations namely indictments and prosecutors' demands. In this case, prosecutors used the first indictment, which is the public prosecutor invoking Article 310 paragraph (4) (four) of Law No.22 of 2009. The Public Prosecutor charges the defendant with a prison sentence of 9 (nine) months in prison, but the charges given by the Public Prosecutor are not appropriate because it is very disproportionate to the consequences resulting from the delik he did and that the causative factors of the criminal offence due to negligence driving a motor vehicle caused others to die in the Jurisdiction of Padangsidimpuan District Court due to several factors including